Application of Building Workers Services in Facing Industrial Revolution 4.0 - Amsyar, Izwan; Cristhopher, Ethan; Rahardja, Untung; Lutfiani, Ninda; Rizky, Agung (Pandawan, 2021)
The services of skilled construction workers are only known around them in the sense that they are not yet widespread in the community, therefore an application is needed that can help construction workers services and can make it easier for the wider community to find construction workers services. The purpose of this research is to build applications as building laborer services based on android and to make construction workers able to compete in this era of industrial revolution 4.0. The method used in this research is the waterfall methodology, where in this methodology each stage of the research is carried out sequentially, starting from the stages of analysis, design, writing program code, testing, and maintenance. This application uses Adobe Illustrator, AirDroid, Android Studio and Sublime Text, but the problem in this research is that it is very difficult to find experienced and professional construction workers and most of these construction workers do not understand the digital world so it is difficult to develop this research in old school community (do not understand the world of technology today).